Medical ethics: What you should know? - Mohd Rizal Abdul Manaf, (Universiti Kebangsaan Malaysia, 2012)
Medical ethics is a system of moral principles that apply values and judgments to the practice of medicine. As a scholarly discipline, medical ethics encompasses its practical application in clinical settings as well as work on its history, philosophy, theology, and sociology. The medical profession has long subscribed to a body of ethical statements developed primarily for the benefit of the patient. A physician must recognize responsibility to patients first and foremost, as well as to society, to other health professionals, and to self. This paper presents some information regarding medical ethics, including the values and principles of ethical conduct. Later the requirements of consent form is presented to guide the researchers before conducting a study.